2003
DOI: 10.1046/j.1524-4725.2003.29052.x
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Lipoma: Analysis of 10 Cases and Explanation of Possible Mechanisms

Abstract: The effect of blunt trauma on fat tissue may be explained by different theories. We summarized possible mechanisms into two groups according to our observations and review of the literature: The first was related to mature adiposities and mainly a mechanical effect, and the second was differentiations of the preadipocytes to lipoma by the promoting factors. We speculate that only traumas that serve as a cause of fat necrosis may trigger the formation of the lipoma, and local inflammation secondary to fat necro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
55
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 26 publications
2
55
1
2
Order By: Relevance
“…The etiology of intramuscular lipoma is unknown. Copcu argued that in rare cases they may arise following trauma (Copcu and Sivrioglu, 2003). Mori et al (2004) reported a type-selective fiber atrophy in 70% of infiltrating lipomas examined by immunohistochemical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of intramuscular lipoma is unknown. Copcu argued that in rare cases they may arise following trauma (Copcu and Sivrioglu, 2003). Mori et al (2004) reported a type-selective fiber atrophy in 70% of infiltrating lipomas examined by immunohistochemical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Since axillary region is one of the most movables of the body, it can be exposed to microtraumas with each movement of the upper limb [8]. In our case it is surgical trauma that has most probably led to recurrence of axillary lipomas into giant axillary lipomas.…”
Section: Discussionmentioning
confidence: 73%
“…Multiple causative factors have been proposed that include genetic [14] traumatic [15] and metabolic [16] triggers. The genetic theory for lipoma formation proposes that spontaneous karyotypic anomalies lead to chromosomal fusion products which promote proliferation of adipocytes [14].…”
Section: Discussionmentioning
confidence: 99%